2022
DOI: 10.3390/biom12091307
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Impact of Deleterious Missense Single Nucleotide Polymorphisms in the NR3C1, CYP3A5, and TNF-α Genes: An In Silico Analysis

Abstract: Human diseases are generally influenced by SNPs (single nucleotide polymorphisms). The mutations in amino acid residues generated by deleterious SNPs contribute to the structural and functional diversity of the encoded protein. Tumor necrosis factor-α (TNF-α), Glucocorticoid receptor gene (NR3C1), and Cytochrome P450 3A5 (CYP3A5) play a key role in glucocorticoid resistance susceptibility in humans. Possible causative mutations could be used as therapeutic targets and diagnostic markers for glucocorticoid resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Many single nucleotide polymorphisms (SNPs) of the NR3C1 gene have already been found to be directly or indirectly related (through GC action or GC resistance) to different mental disorders, especially the stress-related ones and autoimmune diseases such as multiple sclerosis, systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and membranous nephropathy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recent bioinformatics studies have suggested that there are several polymorphisms in the NR3C1 gene, as well as in other genes such as TNF, CYP3A5 and FKBP5 , that have deleterious potential to cause GC resistance [ 14 , 15 ]. Some investigations have suggested a relationship between NR3C1 SNPs rs6189/rs6190, rs41423247, and rs6198 and autoimmune diseases, but studies on GD are still lacking [ 2 , 7 , 8 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many single nucleotide polymorphisms (SNPs) of the NR3C1 gene have already been found to be directly or indirectly related (through GC action or GC resistance) to different mental disorders, especially the stress-related ones and autoimmune diseases such as multiple sclerosis, systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and membranous nephropathy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Recent bioinformatics studies have suggested that there are several polymorphisms in the NR3C1 gene, as well as in other genes such as TNF, CYP3A5 and FKBP5 , that have deleterious potential to cause GC resistance [ 14 , 15 ]. Some investigations have suggested a relationship between NR3C1 SNPs rs6189/rs6190, rs41423247, and rs6198 and autoimmune diseases, but studies on GD are still lacking [ 2 , 7 , 8 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%